639. Vaccination in Kidney Transplant Candidates. (15th December 2022) - Gajurel, Kiran; Ngo, Tue; McCurdy, Lewis
Abstract: Background: Kidney transplant (KT) candidates have historically low immunization rates against recommended vaccines. A retrospective study of KT candidates was conducted to assess contemporary vaccination rates and vaccine uptake during pre-transplant evaluation. Methods: All KT candidates ≥ 18 years referred to Transplant Infectious Disease Clinic for pre-transplant evaluation between January 1, 2020 and August 31, 2020 were retrospectively studied for history of prior vaccination against Tdap, 13 valent pneumococcal conjugate vaccine (PCV13), 23 valent pneumococcal polysaccharide vaccine (PPSV23), Hepatitis A and B (using Hepatitis A total IgG and Hepatitis B surface antibodies as surrogate markers) and recombinant zoster vaccine (RZV). Seropositivity (as a marker of immunity) against measles, mumps, rubella and varicella was also assessed. Results: 109 KT candidates were evaluated (tables 1 & 2). Rates of prior vaccination against Tdap, PCV13 and PPSV23 were 33%, 58%, and 67%. Only 5 (8%) of 61 patients ≥ 50 years of age had received 2 doses of RZV. Thirty (28%) had positive Hepatitis A total IgG and 72 (66%) patients had a positive Hepatitis B surface antibody. Among 37 patients with negative Hepatitis B surface antibody, most had received at least one dose of Hepatitis B vaccine (five were non responders, 19 had had initiated the vaccine series and one had waning antibody response). 79-96% patients had immunity against measles, mumps, rubella and varicella. Patients ≥ 50 years (vs under 50 years) had numerically higher immunization rates against PCV13 and PPSV23 (67% vs 46% and 74% vs 58%) and higher rates of immunity against measles, mumps, rubella and varicella (95% vs 73%; 85% vs 69%, 95% vs 81% and 100% vs 92% respectively). Dialysis patients had a higher Hepatitis B surface antibody compared to non-dialysis patients (78% vs 39%). Only 6 of 109 patients were fully immunized. Among 103 vaccine eligible patients, 99 (96%) agreed to get vaccinated. Table 1 Baseline characteristics of kidney transplant candidates Table 2 Vaccination in kidney transplant candidates Conclusion: KT candidates have low rates of prior immunization against Tdap, PCV13, PPSV23, Hepatitis A and B and RZV but high rates of serological immunity against measles, mumps, rubella and varicella. The vaccine uptake during pre-transplant evaluation was high and it provides an unique opportunity to improve immunization in this population. Disclosures: All Authors : No reported disclosures.